2007
DOI: 10.1063/1.2426940
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical behavior of ultralong multiwalled carbon nanotube mats

Abstract: Carbon nanotubes (CNTs) have been a subject of great interest partially due to their potential for exceptional material properties. Improvements in synthesis methods have facilitated the production of ultralong CNT mats, with lengths in the millimeter range. The increased length of these ultralong mats has, in return, opened the way to greater flexibility to probe their mechanical response. In this work, mats of dense, well-aligned, multiwalled carbon nanotubes were grown with a vapor-phase chemical vapor depo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
53
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(55 citation statements)
references
References 42 publications
1
53
1
Order By: Relevance
“…Similarly, local periodic buckling regions and stiffness of VACNTs under nano-indentation were reported 4 in a low-cyclic compression. These local buckling behaviors of VACNT were observed in many experiments and there are some research studies 3,5,6,[9][10][11][12][13] which employed the classical Euler's column buckling model 14 with the formula: The periodic buckling waves were observed during electrical conductivity characterization of a VACNT block.…”
Section: Introductionmentioning
confidence: 94%
“…Similarly, local periodic buckling regions and stiffness of VACNTs under nano-indentation were reported 4 in a low-cyclic compression. These local buckling behaviors of VACNT were observed in many experiments and there are some research studies 3,5,6,[9][10][11][12][13] which employed the classical Euler's column buckling model 14 with the formula: The periodic buckling waves were observed during electrical conductivity characterization of a VACNT block.…”
Section: Introductionmentioning
confidence: 94%
“…Such remarkable flexibility and resilience of nanotubes potentially make them an ideal low‐weight foamlike material once they are organized into specific 3D architectures, such as aligned 3D arrays or foams. Recent work has demonstrated that vertically aligned MWNT arrays exhibit super‐compressible behavior, in which individual nanotubes act as strong nanoscale struts and the internanotube spaces act as interconnected open‐air cells 121, 122. The compressed nanotubes could be collectively squeezed by buckling and folding themselves like springs.…”
Section: Mechanical Properties Of Cnt Assembliesmentioning
confidence: 99%
“…have the ability to recover from large strains of up to 80% upon unloading [10,15]. Their deformation response is highly localized and in compression these foams support the formation of sequential buckles, originating from anisotropic, graded functional properties.…”
Section: Introductionmentioning
confidence: 98%